Spondias tuberosa trees grown in tropical, wet environments are more susceptible to drought than those grown in arid environments - Camargos Antunes, Werner; Rêgo Mendes, Keila; Rodrigues de Melo Chaves, Agnaldo; Ometto, Jean Pierre; Jarma-Orozco, Alfredo; Pompelli, Marcelo Francisco (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2016)
In this study, we investigated the different responses of Spondias tuberosa (umbu) trees, which grow in two different ecological life zones in northeast Brazil: tropical wet and tropical arid ecosystems. We evaluated the responses of plants grown under humid and dry conditions by measuring photosynthesis, water status, fluorescence parameters, carbon isotopes and antioxidant systems activity. The highest net photosynthesis values were recorded simultaneously with the lowest VPD values. The highest internal-to-ambient CO2 concentration and the absence of typical changes in the fluorescence parameters suggested the onset of a nonstomatal limitation in photosynthesis. Our results showed that umbu plants can adjust their antioxidant activity during the dry season as a defensive strategy against the deleterious effects of water stress. This evidence is supported by the observed modifications in the pigment concentrations, increased accumulation of hydrogen peroxide and malondialdehyde, high levels of electrolyte leakage, increased antioxidant activity, and decreased carbon isotope discrimination in the umbu trees during the dry season. Supported by multivariate analysis of variance, significantly effect of interaction between categorical “months of collect and location” predicts a strong “dry season effect” on our dataset. Taken together, our data show that umbu trees grown in a wet tropical environment are more susceptible to drought compared with their tropical arid counterparts.